Beginning ASP.NET 4 in VB 2010 - MacDonald, Matthew (Apress, 2012)
This book explores ASP.NET, which is a core part of Microsoft’s .NET Framework. The .NET Framework is not a single application—it’s actually a collection of technologies bundled into one marketing term. The .NET Framework includes languages such as C# 2010 and VB 2010, an engine for hosting programmable web pages, a model for interacting with databases (ADO.NET), a higher-level framework for performing queries (LINQ and the Entity Framework), and a class library stocked with tools for everything from reading files to validating a password. To master ASP.NET, you need to learn about each of these ingredients.